Bone Response to Weight Loss Following Bariatric Surgery - Mele, Chiara; Caputo, Marina; Ferrero, Alice; Daffara, Tommaso; Cavigiolo, Beatrice; Spadaccini, Daniele; Nardone, Antonio; Prodam, Flavia; Aimaretti, Gianluca; Marzullo, Paolo (Frontiers in Endocrinology, 2022)
Obesity is a global health challenge that warrants effective treatments to avoid its multiple comorbidities. Bariatric surgery, a cornerstone treatment to control bodyweight excess and relieve the health-related burdens of obesity, can promote accelerated bone loss and affect skeletal strength, particularly after malabsorptive and mixed surgical procedures, and probably after restrictive surgeries. The increase in bone resorption markers occurs early and persist for up to 12 months or longer after bariatric surgery, while bone formation markers increase but to a lesser extent, suggesting a potential uncoupling process between resorption and formation. The skeletal response to bariatric surgery, as investigated by dual-energy X-ray absorptiometry (DXA), has shown significant loss in bone mineral density (BMD) at the hip with less consistent results for the lumbar spine. Supporting DXA studies, analyses by high-resolution peripheral quantitative computed tomography (HR-pQCT) showed lower cortical density and thickness, higher cortical porosity, and lower trabecular density and number for up to 5 years after bariatric surgery. These alterations translate into an increased risk of fall injury, which contributes to increase the fracture risk in patients who have been subjected to bariatric surgery procedures. As bone deterioration continues for years following bariatric surgery, the fracture risk does not seem to be dependent on acute weight loss but, rather, is a chronic condition with an increasing impact over time. Among the post-bariatric surgery mechanisms that have been claimed to act globally on bone health, there is evidence that micro- and macro-nutrient malabsorptive factors, mechanical unloading and changes in molecules partaking in the crosstalk between adipose tissue, bone and muscle may play a determining role. Given these circumstances, it is conceivable that bone health should be adequately investigated in candidates to bariatric surgery through bone-specific work-up and dedicated postsurgical follow-up. Specific protocols of nutrients supplementation, motor activity, structured rehabilitative programs and, when needed, targeted therapeutic strategies should be deemed as an integral part of post-bariatric surgery clinical support.